Special education transition services for students with disabilities - Bakken, Jeffrey P.; Obiakor, Festus E. (Advances in special education, 2019)
While services for students with disabilities have been vastly improved in recent years, and research has created far greater awareness for the issues they face, there are still many obstacles to overcome as these students progress through the education system. This book discusses the considerable challenges these students conquer in education, varying relationships with teachers and academics, learning resources, and everyday social situations. Beginning with an introduction to transition services and students with disabilities, this invaluable text goes on to discuss a wide range of disability topics. Leaders in the field of transition services present recent research on students with learning disabilities, deaf/hard of hearing students, those who have visual impairments, autistic students, those with extensive support needs, physical disabilities, and more. This book is an excellent resource for special education researchers, scholars, practitioners, and professionals who teach and serve students with disabilities.